The cuff and the collar : a contemporary representation of seventeenth century symbols of power and oppression at the Cape of Good Hope - Kruger, Carla Maxine (Stellenbosch : Stellenbosch University, 2014)
Thesis (MA(VA))--Stellenbosch University, 2014.